Novel microbial-electrochemical filter with a computer-feedback pH control strategy for upgrading biogas into biomethane. (July 2021) - Charles, Wipa; Cord-Ruwisch, Ralf; Ho, Goen
Graphical abstract: Highlights: Novel design and operation of reactor for bioelectromethanogenesis process. Computer-feedback pH control linking CO2 feed directly to the OH − production. Ability to maintain the process at a constant designed pH. Ability to potentially operate at high applied potential and current. Abstract: A novel microbial-electrochemical filter was designed and operated based on a combined microbial electrolysis cell and bio-trickling filter principles with the aim to maximize gas–liquid mass-transfer efficiency and minimize costs associated with bubbling biogas through liquid-filled reactor. CO2 /biogas feed to the MEF was done via a computer-feedback pH control strategy, linking CO2 feed directly to the OH − production. As a result current efficiency was constant at around 100% throughout the period of experiments. CO2 from biogas was almost completely removed at cathodic pH setpoint of 8.5. Maximum CO2 removal rate was 14.6 L/L/day (equivalent to 29.2 L biogas/L/day). Net energy consumption was around 1.28 kWh/Nm 3 CO2 or 0.64 kWh/m 3 biogas (maximum 49% energy efficiency). An ability to maintain a constant pH means elevated pH from increasing applied potential (current) is no longer an issue. The process can potentially be up-scaled and operated at a much higher current and therefore CO2 removal rate.